ANALISIS KEPUTUSAN PEMBELIAN BERDASARKAN ATRIBUT KUALITAS PENJUALAN - Muhammad Brilian Fajar; Argosawwa Rizqahu; Raisa Kiyasa Paramitha; Lidya Devega; Juhaeri Juhaeri (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
Behind consumer purchases there are benefits to be gained by the company. Therefore, there needs to be a measurable effort in marketing the product, so that consumers are interested and decide to make a purchase, resulting in increased sales. Several factors that can be taken into consideration in improving purchasing decisions are improving the quality aspect. Based on this phenomenon, this research was conducted to test the truth that might occur through a series of scientific methods, namely using a quantitative approach with multiple linear regression analysis. The research sample is consumers (Muslim women) using the Shopee application who make purchases of Muslim clothing products. The number of samples used was 100 respondents with a simple random technique. The results showed that product quality is the main factor in purchasing decisions, then the guarantee quality factor, and finally service quality. These findings explicitly explain the characteristics of online purchases, where consumers remain focused on the quality of a product they want to buy, and to ensure that consumers need guarantees for the product. Meanwhile, service is a supporting factor that strengthens consumer confidence to make purchases.